MEMAHAMI STRATEGI PEMBERANTASAN KORUPSI DI INDONESIA - Septiana Dwiputrianti (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2009)
Corruption is not far from the action of stealing or blacking out. However, the complexity of corruptions’ structure and elements is different. Corruption is closer to any action of stealing or blacking out public money that can cause any state loss. Since the reformation era in Indonesia, the government of Republic Indonesia has taken some efforts to reduce the practice of corruption in public sector. Recently, the strategy of combating corruption in government sector under SBY and Budiono’s leadership become undertaken more seriously. The new regulations have been issued as the laws basis to combat the corruption. Moreover, the Corruption Eradicating Commission (Komisi Pemberantasan Korupsi or KPK) has been existed as an independent institution that has authority to investigate any indication of corruption. Based on that background, this article has significant contribution to provide better understanding about corruption in more detail, from its definitions, regulations, causes, impacts, anti-corruption actions until some recent cases in Indonesia. The rigoous documentation reviews, from laws, regulations, government documentations, academics references and printed medias have applied as the primary data.